The effect of skin-to-skin contact on early initiation of breastfeeding among women in Vietnam - Hoang Thi Nam Giang; Le Tho Minh Hieu; Do Thi Thuy Duy; Mai Thi Phuong; Tran Dinh Trung (Elsevier, 2024)
Aim: To describe prevalence of early initiation of breastfeeding and associated factors among Vietnamese mothers. Methods: A self-administered questionnaire was used to survey 1812 mothers whose infants were aged 0 to less than 30 months in multi-center Vietnam. Multivariate logistic regression was performed to identify factors associated independently with early initiation of breastfeeding. Results: Prevalence of early initiation of breastfeeding was 57.2 % and this prevalence was higher in female infants compared with male infants (p = 0.004). Factors associated with increased odds of early initiation of breastfeeding include female infants (aOR: 1.33; 95%CI: 1.06 to 1.68) living in urban areas (aOR: 1.34, 95%CI: 1.05 to 1.71), giving birth in private hospitals (aOR: 1.94, 95%CI: 1.25 to 3.03), vaginal birth (aOR: 1.70, 95%CI: 1.34 to 2.16). Factors associated with decreased odds of early initiation of breastfeeding include higher educational level, mother's weight gain during pregnancy, and infant complication at birth. Compared with mothers who had not experienced skin-to-skin contact with their babies, the prevalence of early initiation of breastfeeding was higher in mothers who experienced <15 min (aOR: 2.03, 95%CI: 1.32 to 3.14), 15-90 min (aOR: 6.33, 95%CI: 4.11 to 9.76), and >90 min (aOR: 10.98, 95%CI: 6.79 to 17.75). Conclusion: Focusing on modifiable factors should be a key priority to help improve early initiation of breastfeeding practice.